Urban–rural differences in perception of trees described by parents bringing up children in Warsaw and Jedlińsk, Poland - Wojnowska-Heciak,Magdalena; Błaszczyk,Magdalena; Suchocka,Marzena; Kosno-Jończy,Joanna (PeerJ, 2020)
Parents’ attitudes to trees and nature are reflected not only in their children’s outdoor activity, but also in the way they perceive, learn and value the environment. One hundred and eleven respondents, divided into two groups by place of residence, assessed statements in a survey questionnaire. Two groups of questions aimed at evaluating tree benefits and disservices as perceived by urban and rural parents, and identifying their preferences concerning outdoor activity of their children. Tree benefits and disadvantages were grouped into five categories (social, economic, environmental, health and aesthetic). Both urban and rural parents presented similar attitudes to trees as well as to their children’s play environments. Among 37 statements concerning tree benefits, only five revealed statistically significant differences. The most important difference appeared in the way urban and rural parents perceived the aspects of danger. Trees were not perceived as posing any risk on playgrounds for city residents, who—unlike villagers—opposed to the removal of trees from playgrounds.
Keywords: Parents; Attitudes towards trees; Preference of trees; Sociodemographic differences; Social survey